2016
DOI: 10.1002/art.39643
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA Methylation and Reduced Expression of Transcription Factors in Human Osteoarthritis Cartilage

Abstract: Objectives To analyze the methylome of normal and osteoarthritis (OA) knee articular cartilage and determine the role of DNA methylation in the regulation of gene expression in vitro. Methods DNA was isolated from human normal (N=11) and OA (N=12) knee articular cartilage and analyzed by an Infinium HumanMethylation450 BeadChip methylation array. To integrate methylation and transcription, RNAseq was performed on normal and OA cartilage validated by qPCR. Functional validation was performed in the human TC28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 56 publications
(85 reference statements)
5
76
0
Order By: Relevance
“…49 As of yet, none of the remaining DMPs and their annotated genes have been identified as candidate methylation loci in human OA studies. [4][5][6][7][8][9][10] Nevertheless, some DMPs are located in close proximity to genes that have been previously associated with OA, including CRTC1 50 , CRLF1 51 , COMP 52 , SMAD9 53,54 , and ALOX12 55,56 (Table 1). However, the mechanisms by which these DMPs might influence the expression of these distally related genes is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 As of yet, none of the remaining DMPs and their annotated genes have been identified as candidate methylation loci in human OA studies. [4][5][6][7][8][9][10] Nevertheless, some DMPs are located in close proximity to genes that have been previously associated with OA, including CRTC1 50 , CRLF1 51 , COMP 52 , SMAD9 53,54 , and ALOX12 55,56 (Table 1). However, the mechanisms by which these DMPs might influence the expression of these distally related genes is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DNA methylation which regulates gene expression, is thought to play an influential role in the development of degenerative skeletal disorders like OA. [4][5][6][7][8][9][10] Animal models, such as mice, rats, rabbits, guinea pigs, dogs, sheep, goats, and horses, have been essential in discerning some of the processes inherent to OA development. 11,12 Nevertheless, all of these animals are limited in their abilities to fully inform our understanding of human OA, so the search to find a gold standard animal model for OA is still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…152 One study has shown an overall increase in methylation accompanied by reduced expression of transcription factors in OA compared to healthy cartilage. 153 Changes in DNA methylation associated with OA progression are also observed in subchondral bone, with an enrichment of genes involved in morphogenesis and development of the skeletal system in OA samples, 154 highlighting the contributions of developmental pathways in the disease context. Importantly, the transcription of genes encoding regulatory factors, including DIO2, SOX9, RUNX2, ELF3, and GDF5, is in part modulated by DNA methylation.…”
Section: Figure 4 Modulation Of Chondrocyte Hypertrophy By Canonicalmentioning
confidence: 99%
“…However, RNA-seq has the unique ability to determine the relative expression levels of all genes within a cell or tissue. This technique has not yet been widely used on articular cartilage, [8][9][10][11][12][13][14] and to the best of our knowledge, the transcriptome-wide profile of articular cartilage obtained from healthy knee joints has not been reported.…”
mentioning
confidence: 99%